2012
DOI: 10.1016/j.jviscsurg.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intussusceptions revealing metastases from renal carcinoma to the small intestine

Abstract: Malignant tumors of the kidney represent rare primary intestinal metastases. They occur in 4% of cases. These intestinal metastases are mainly the small intestine; colon is a rare achievement. We report a case of small intestine metastatic of a tubulo-pappilary carcinoma revealed by a multiple intussusception a year after nephrectomy. The cross-sectional imaging (ultrasound and CT) was the gold standard for positive diagnosis of intussusception and the nature of secondary underlying tumor. Intestinal metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Very few cases of multiple intussusception caused by RCC metastases have been reported [ 7 10 ]. Some authors suspect, however, that many cases may have been overlooked in the context of terminal disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases of multiple intussusception caused by RCC metastases have been reported [ 7 10 ]. Some authors suspect, however, that many cases may have been overlooked in the context of terminal disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that approximately 69% of canine carcinomas of the kidney metastasize to other organs via the lymphatic or blood vessels [20]. Though RCC does not have a propensity for gastrointestinal metastasis, there are several reports of its metastasis to the gastrointestinal tracts in humans [21,22].Third, apart from physical compression or embolus formation from metastasis, RCCs may attribute to the incidence of IL, which is associated with either the functional alteration of kidney or pathological conditions due to the RCC itself. Albeit uncommon, it has been reported that RCC can be associated to gastrointestinal diseases [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most of gastro-intestinal lymphomas cause circumferential involvement of the bowel wall [34]. Metastatic tumors of SB (Figures 5(c) and 5(d)) as well as benign tumors are sporadically visualised by TUS due to intussusception caused by these tumors [35]. …”
Section: Tus In Detection Of Small Bowel Tumorsmentioning
confidence: 99%
“…In adult population are intussusceptions sporadically incidentally seen during abdominal TUS, or in SB inflammations, celiac disease, tumors of SB. Frequently are self-limiting, idiopathic or related to celiac or Crohn's disease, in about 25% are asymptomatic [41], however some can hide benign or malignant or metastatic tumors [35, 42]. Other imaging methods (CT, MRI) are indicated in suspicion of tumour(s).…”
Section: Tus In Intussusception Of Small Bowelmentioning
confidence: 99%